Value of computed tomography and magnetic resonance imaging in the treatment of a calcifying epithelial odontogenic (Pindborg) tumour - J.J.L. Cross,* R.J.J. Pilkington, N.M. Antoun, D.M. Adlam (Blackwell Synergy, 2000)
The calcifying epithelial odontogenic tumour was described in 1958 by Pindborg and the lesion is more commonly known as the Pindborg tumour. Its clinical features, radiographic appearances, and histological features (Table 1) have been described but to our knowledge the appearances on computed tomography (CT) and magnetic resonance (MR) images have not previously been reported.